(untitled) (Universal International Scientific Journal, 2026)
This article provides a comprehensive analysis of the current state of inclusive education in Kyrgyzstan. It examines the legal, organizational, and socio-psychological aspects of implementing inclusive practices in the country’s education system. Particular attention is paid to the issues of teacher training, creating a barrier-free environment, and overcoming social stereotypes. Psychological educational methods are also analyzed as a means of forming an inclusive culture in society. Specific solutions to the identified problems are proposed at a systemic level.